Efficacy and Tolerability of Subcutaneous Methylnaltrexone in Patients with Advanced Illness and Opioid‐Induced Constipation: A Responder Analysis of 2 Randomized, Placebo‐Controlled Trials. Issue 6 (10th May 2014) - Nalamachu, Srinivas R.; Pergolizzi, Joseph; Taylor, Robert; Slatkin, Neal E.; Barrett, Andrew C.; Yu, Jing; Bortey, Enoch; Paterson, Craig; Forbes, William P.
Abstract Background Subcutaneous methylnaltrexone is efficacious and well tolerated in inducing bowel movements in patients with advanced illness and opioid‐induced constipation (OIC); factors determining optimal responsiveness to OIC treatment, however, have not been elucidated. This post hoc responder analysis examined the influence of demographic and baseline characteristics on methylnaltrexone efficacy and tolerability in this population. Methods Data were pooled from 2 randomized, double‐blind, placebo‐controlled, phase 3 studies of subcutaneous methylnaltrexone (0.15 and 0.30 mg/kg) [ClinicalTrials.gov identifiers: Study 301 – NCT00401362; Study 302 – NCT00402038]. Subgroup analyses of the primary outcome, percentage of patients with rescue medication‐free bowel movements (RFBM) within 4 hours of first dose, were conducted for age, sex, primary diagnosis, baseline constipation‐related distress score, and baseline oral morphine equivalent dose. Results More than 50% of 165 patients treated with either methylnaltrexone dose experienced a RFBM within 4 hours vs. 14.6% of 123 placebo‐treated patients (P < 0.0001 for both methylnaltrexone doses vs. placebo). Methylnaltrexone response was significantly greater than placebo response in all subgroups (P < 0.01). The largest differences vs. placebo were observed for patients taking methylnaltrexone 0.30 mg/kg with a noncancer primary diagnosis (70.0% [methylnaltrexone] vs. 12.8% [placebo]; P < 0.001) and for patients taking methylnaltrexone 0.30 mg/kg maintained on ≥ 150 mg/day baseline morphine equivalent doses (73.3% vs. 16.7%; P < 0.0001). Common adverse events were abdominal pain (pooled methylnaltrexone: 27.9%, placebo: 9.8%), flatulence (13.3%, 5.7%), and nausea (10.9%, 4.9%). Tolerability was comparable across subgroups. Conclusion Subcutaneous methylnaltrexone provides a rapid, robust, and consistent RFBM response in patients with advanced illness and OIC. Methylnaltrexone 0.30 mg/kg may elicit particularly favorable responses in select patient populations.